Genetic variants associated with susceptibility to idiopathic pulmonary fibrosis in people of European ancestry: a genome-wide association study. Issue 11 (November 2017) - Allen, Richard J; Porte, Joanne; Braybrooke, Rebecca; Flores, Carlos; Fingerlin, Tasha E; Oldham, Justin M; Guillen-Guio, Beatriz; Ma, Shwu-Fan; Okamoto, Tsukasa; John, Alison E; Obeidat, Ma'en; Yang, Ivana V; et al.
Summary: Background: Idiopathic pulmonary fibrosis (IPF) is a chronic progressive lung disease with high mortality, uncertain cause, and few treatment options. Studies have identified a significant genetic risk associated with the development of IPF; however, mechanisms by which genetic risk factors promote IPF remain unclear. We aimed to identify genetic variants associated with IPF susceptibility and provide mechanistic insight using gene and protein expression analyses. Methods: We used a two-stage approach: a genome-wide association study in patients with IPF of European ancestry recruited from nine different centres in the UK and controls selected from UK Biobank (stage 1) matched for age, sex, and smoking status; and a follow-up of associated genetic variants in independent datasets of patients with IPF and controls from two independent US samples from the Chicago consortium and the Colorado consortium (stage 2). We investigated the effect of novel signals on gene expression in large transcriptomic and genomic data resources, and examined expression using lung tissue samples from patients with IPF and controls. Findings: 602 patients with IPF and 3366 controls were selected for stage 1. For stage 2, 2158 patients with IPF and 5195 controls were selected. We identified a novel genome-wide significant signal of association with IPF susceptibility near A-kinase anchoring protein 13 ( AKAP13 ; rs62025270, odds ratio [OR] 1·27 [95% CI 1·18–1·37], p=1·32 × 10 −9 ) and confirmed previously reported signals, including in mucin 5B ( MUC5B ; rs35705950, OR 2·89 [2·56–3·26], p=1·12 × 10 −66 ) and desmoplakin ( DSP ; rs2076295, OR 1·44 [1·35–1·54], p=7·81 × 10 −28 ). For rs62025270, the allele A associated with increased susceptibility to IPF was also associated with increased expression of AKAP13 mRNA in lung tissue from patients who had lung resection procedures (n=1111). We showed that AKAP13 is expressed in the alveolar epithelium and lymphoid follicles from patients with IPF, and AKAP13 mRNA expression was 1·42-times higher in lung tissue from patients with IPF (n=46) than that in lung tissue from controls (n=51). Interpretation: AKAP13 is a Rho guanine nucleotide exchange factor regulating activation of RhoA, which is known to be involved in profibrotic signalling pathways. The identification of AKAP13 as a susceptibility gene for IPF increases the prospect of successfully targeting RhoA pathway inhibitors in patients with IPF. Funding: UK Medical Research Council, National Heart, Lung, and Blood Institute of the US National Institutes of Health, Agencia Canaria de Investigación, Innovación y Sociedad de la Información, Spain, UK National Institute for Health Research, and the British Lung Foundation.